Temples of luxury.
1 online resource (xiii, 480 pages)
Keywords: This two-volume collection of British primary sources examines institutions such as hotels, inns, arcades, bazaars, co-operatives, shops and department stores in the long nineteenth century, which were often coded as ⁰́₈luxurious⁰́₉. This period was marked not only by an increase of individual consumerism but also by the institutionalisation of opulent, often purpose-built spaces such as the much-admired new grand hotels, supposedly an American invention, and department stores, modelled on the French grands magasins. These environments were tied to leisure (no longer a prerogative of the upper classes) and thus to modernity. In addition to addressing the luxurious side of these institutions, including architectural innovation and interior decoration, we also consider the other side of luxury, examining the experience of staff and period debates over the morality of consumption. This edition seeks to explore a fascinating but hitherto often neglected side of the British nineteenth century by bringing together a collection of annotated primary texts and visual material documenting these ⁰́₈temples of luxury⁰́₉ as they were seen by their contemporaries.